Proinflammatory TNF Alfa TNF Beta, Interleukin 6, Anti-inflammatory Interleukin 10 Cytokines and the Associated Cytokine Imbalance in the Specific Immune Primed Rabbit Models with Streptococcus Pneumonia Serotype 1 and Serotype 6 Capsules - Shnawa, Ibrahim M S; Al-Janabi, A A J (British Journal of Healthcare and Medical Research, 2025)
The capsular polysaccharide Type 1 and type 6 of the human clinical local pneumotropic isolates of Streptococcus pneumoniae were separated, characterized and purified. Then quantified to concentrations of 1 mg/ml. To be ready as immunogens they were admixed with an equal volume of lanline. These were standing as the test immunogens. The test immune system was that of rabbits. The test rabbit groups were assigned as C 1 group,C6 group and saline S control group each of five animals. The test rabbit groups C 1 and C6 were primed once through intramuscular route separately with capsule-lanoline mixtures and left for 21 days, then bleed. Sera were saved from the primed rabbits blood samples in 0.5 ml aliqoutes till use. Trachial mucosal immunoglobulin were separated, partially characterized and kept in alqoutes of 0.5 amounts in forml normal saline till use. One step sandawich eliza technique for TNF alfa, TNF beta, IL6 and IL10 were performed for both sera and mucosal globuilin of the primed rabbits and controls. The immune features of the capsule-lanline primed rabbits were found as; capsules were weak immunogen needs adjuvant in order to become good immunogen, cytokine responses were serotype dependent, mucosal cytokines have shown to be of higher levels than systemic responses, C1 was higher immune convertor than C 6, and both associated with cytokine imbalance towards pro-inflammatory cytokines.